2006 International Electron Devices Meeting 2006
DOI: 10.1109/iedm.2006.346902
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensionally Stacked NAND Flash Memory Technology Using Stacking Single Crystal Si Layers on ILD and TANOS Structure for Beyond 30nm Node

Abstract: For the first time, the 3 dimensionally stacked NAND Flash memory, is developed by implementing S 3 ( Single-crystal Si layer Stacking ) technology, which was used to develop S 3 SRAM previously. The NAND cell arrays are formed on the ILD as well as on the bulk to double the memory density without increasing the chip size. The feasibility of the technology was proven by the successful operation of 32 bit NAND Flash memory cell strings with 63nm dimension and TANOS structures. The novel NAND cell operational sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…In order to limit wafer cost, number of vertical layers must be as low as possible and, to compensate this limitation, it is fundamental to use small single cells. Many publications using this array organization have been presented [13,14]. Flexibility and reuse of know-how developed with planar CT cells are probably the reasons to explain the remarkable activity in this area.…”
Section: D Stacked Architecturementioning
confidence: 96%
“…In order to limit wafer cost, number of vertical layers must be as low as possible and, to compensate this limitation, it is fundamental to use small single cells. Many publications using this array organization have been presented [13,14]. Flexibility and reuse of know-how developed with planar CT cells are probably the reasons to explain the remarkable activity in this area.…”
Section: D Stacked Architecturementioning
confidence: 96%
“…The 3D stackable NAND Flash devices (Jung et al 2006;Lai et al 2006) were demonstrated in 2006, where both single crystal silicon (Jung et al 2006) (by an epitaxial Si process) and poly-silicon TFT (Lai et al 2006) charge-trapping SONOS-type devices were demonstrated, as shown in Fig. 4.1.…”
Section: Brief Comparison Of Various 3d Nand Flash and A General Costmentioning
confidence: 99%
“…It forms transistors inside on-chip interconnect layer [3], on poly-silicon films [18], or on single-crystal silicon films [32], [33]. Although a drastically high vertical interconnect density can be realized, it is not readily compatible to existing fabrication processes and is subject to severe process temperature constraints that tend to dramatically degrade the circuit electrical performance.…”
Section: Transistor Build-up 3d Technologymentioning
confidence: 99%